Preparing and sharing the table: The invisibility of women and enslaved domestic workers in Luke's Last Supper. (November 2020) - Cobb, Christy
In biblical narratives that involve food, women and enslaved domestic workers were very involved in the planning, preparation, and the partaking of meals, even though they are mostly invisible in biblical texts. To make these women and enslaved workers visible, I closely examine the narrative of the Last Supper, or Passover, in the Gospel of Luke (22.7–38). In this gospel, women are present as followers of Jesus and are present with Jesus throughout his ministry, thus their presence at the Last Supper would be expected. In addition, enslaved characters fill the Gospel of Luke as a part of parables as well as within the narrative. In the conclusion of this article, I reimagine the scene of Luke's Last Supper as it might have happened historically, with women and enslaved persons made visible in the preparations and during the meal itself.